2023
DOI: 10.1002/ejoc.202300626
|View full text |Cite
|
Sign up to set email alerts
|

Julia‐Kocienski Olefination in the Synthesis of Trisubstituted Alkenes: Recent Progress

Konstantinos A. Ouzounthanasis,
Stergios R. Rizos,
Alexandros E. Koumbis

Abstract: Julia‐Kocienski olefination, a coupling reaction between a carbonyl component and a sulfone partner, has been emerged as a powerful synthetic tool in the preparation of several organic compounds. A number of interesting examples involving particularly the preparation of trisubstituted alkenes along with important observations regarding the stereoselectivity of those reactions have been recently reported. This reviewing work covers the literature for the period 2016‐2022 and describes in a comprehensive way the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 163 publications
(197 reference statements)
0
1
0
Order By: Relevance
“…The main drawbacks of Julia–Lythgoe olefination, namely the steric requirement-driven ( E / Z ) selectivity and the two-pot protocol, were in 1993 overcome by Silvestre Julia [ 20 , 21 ] (brother of Mark Julia). Their modification of the standard Julia–Lythgoe olefination protocol was based on the replacement of the phenylsulfonyl group with the benzo[ d ]thiazol-2-ylsulfonyl (BT) group ( Scheme 2 ) [ 22 , 23 , 24 ]. The common features of the new transformation of the Julia–Lythgoe olefination reaction are the first two steps: (1) metalation; (2) the addition of metalated sulfone 11 to aldehyde 12 .…”
Section: Origins and Mechanism Of The Julia–kocienski Olefination Rea...mentioning
confidence: 99%
“…The main drawbacks of Julia–Lythgoe olefination, namely the steric requirement-driven ( E / Z ) selectivity and the two-pot protocol, were in 1993 overcome by Silvestre Julia [ 20 , 21 ] (brother of Mark Julia). Their modification of the standard Julia–Lythgoe olefination protocol was based on the replacement of the phenylsulfonyl group with the benzo[ d ]thiazol-2-ylsulfonyl (BT) group ( Scheme 2 ) [ 22 , 23 , 24 ]. The common features of the new transformation of the Julia–Lythgoe olefination reaction are the first two steps: (1) metalation; (2) the addition of metalated sulfone 11 to aldehyde 12 .…”
Section: Origins and Mechanism Of The Julia–kocienski Olefination Rea...mentioning
confidence: 99%
“…More recently, it was found that the issue with the stereoselective double bond construction can be solved by employing the Julia–Kocienski olefination. 19–21 In this manner, the formal total synthesis of limazepine E ( 11 ) 22 as well as oxo-prothracarcin ( 6 ), oxo-tomaymycin ( 7 ), and boseongazepine B ( 8 ) was successfully accomplished. 23 Herein we report a further extension of this methodology enabling access to the key C2 ethylidene group-possessing PBD natural products and their precursors in only 3 linear steps.…”
mentioning
confidence: 99%